Hemipteroseius adleri Costa, 1968 collected on red firebug: the first record of the family Otopheidomenidae Treat, 1955 (Acari: Mesostigmata) in Hungary - Kontschán, J. (Opuscula Zoologica Instituti Zoosystematici et Oecologici Universitatis Budapestinensis, 2010)
The parasitic mite Hemipteroseius adleri Costa, 1968 was collected on red firebug, Pyrrhocoris apterus (Linnaeus,1758) for the first time in Hungary. Short description and drawings of the specimens are presented.